(untitled) (Journal of Advanced Veterinary and Animal Research, 2025)
Objective: Animal migration can spread different diseases from farm to farm without being noticed. Despite bovine brucellosis being endemic in Myanmar, seroprevalence and risk related to farmers’ behaviors and cattle migration remain unclear. Thus, understanding brucellosis in seasonal cattle migration is essential to avoid negative economic and public health outcomes. As seasonal cattle movement is done to satisfy local environmental limits, Brucellosis is predisposed in cattle herds of the Central Dry Zone of the country. Materials and Methods: In this study, farmer characteristics and seasonal cattle movement practices were investigated for bovine brucellosis prevalence in three Central Myanmar regions from July to August 2022. Blood samples were taken for the Rose Bengal Plate Test to detect brucellosis prevalence. Results: Seasonal migratory farmers had a lower education level, more family members, more cattle heads, and higher income from cattle raising. Influences on disease knowledge included frequent veterinary access (7.02%) and limited disease control training (17.39%). Young farmers with low educational level (p < 0.01), more family members (p < 0.01), less farming experience (p < 0.01), fewer cattle (p < 0.01), cow abortion cases (p < 0.01), farming practices from veterinary access (p < 0.01), and longer migratory distances to grazing pastures (p < 0.01) have higher possibilities to get prevalence of bovine brucellosis at farm level. Conclusion: This study found that farmers’ characteristics, migratory practices, migration distance, and abortion history influence Brucellosis prevalence at the farm level. Migratory farmers need farmer collaboration and veterinary training to learn effective farming practices. Access to veterinary services and farmer awareness campaigns about livestock migration risks are essential. J. Adv. Vet. Anim. Res., 12(2): 350–360, June 2025 http://doi.org/10.5455/javar.2025.l903